Between Punishment and Resistance. Representations of the Slave Body in Joaquim Machado de Assis’s «Father against Mother» (1906) - Espinoza, Jean Paul (2023)
Based on Michel Foucault’s theoretical contributions on power, this paper aims to address a short story by the Brazilian writer Joaquim Machado de Assis: «Father against Mother» (1906). This text presents a story that revolves around slavery, focusing especially on the practices of punishment and the role of the body in these dynamics. My hypothesis is that, in this story, slave subjects are represented as seeking to produce docile bodies through disciplinary mechanisms: punishments, detention and torture, mainly. In this sense, I am interested in exploring the techniques of control exercised by the masters to maintain their repressive authority. However, my interpretation does not intend to leave aside the acts of resistance that are at play in any regime of power. Therefore, my analysis also considers the brief but significant manifestations of transgression developed by the slaves in the text. The escape attempts and displays of insubordination show that the subalterns are not willing to fit into models of full obedience. In this framework, what my object of study demonstrates is that the functioning of power and the struggles of resistance are necessarily inscribed in the domains of the body: there is, in fact, no system of slavery without an anatomopolitics.